An In Situ Temperature-Dependent Study of La2O3 Reactivation Process - Zhou, Xiaohong; Vovk, Evgeny I.; Liu, Yang; Guan, Cairu; Yang, Yong (Frontiers in Chemistry, 2021)
Lanthanum containing materials are widely used in oxidative catalytic and electrocatalytic reactions such as oxidative coupling of methane (OCM) and solid oxide fuel cells (SOFCs). However, many of these materials are highly susceptible to air contamination which means ex situ characterization results generally cannot be associated with their reactivity. In this study, the activation processes of an in situ prepared bulk La2O2CO3 sample and an ex situ as prepared La(OH)3 sample , are in situ investigated by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and online mass spectroscopy (MS). Results indicate that the La2O2CO3 sample, during linear heating to 800°C, always contains some carbonates near the surface region, which supports a two-step model of bulk carbonate decomposition through surface sites. The La(OH)3 sample structure evolution is more complex due to contaminations from air exposure. Together with TGA results, online mass analysis of water and CO2 signals loss showed that three major catalyst structure phase change steps and a preheating up to 800°C is required for the as prepared material transferred to La2O3. This process is carefully investigated combining the three in situ methodologies. XPS and XRD data further reveal transformations of variety of in situ surface structures and forms including hybrid phases with hydroxyl, carbonates and oxide as the sample heated to different temperatures within the range from 200 to 800°C. The results provide useful insights on the activation and deactivation of La contained materials.